2018
DOI: 10.3390/jimaging4040052
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Remote Sensing on Crop Models: A Review

Abstract: Abstract:Crop growth models simulate the relationship between plants and the environment to predict the expected yield for applications such as crop management and agronomic decision making, as well as to study the potential impacts of climate change on food security. A major limitation of crop growth models is the lack of spatial information on the actual conditions of each field or region. Remote sensing can provide the missing spatial information required by crop models for improved yield prediction. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(120 citation statements)
references
References 111 publications
(131 reference statements)
0
87
0
2
Order By: Relevance
“…In order to ensure today's food security and in the coming decades, efforts have been made on establishment of crop simulation models aimed at predicting growth, development and yield potential of a crop under certain environmental conditions (Basso et al, 2013;Wang et al, 2018;. Several dynamic crop simulations models (CSMs) have been developed and used widely to study physiological, physical and chemical processes of crop productivity under a changing climate (Kasampalis et al, 2018;Shi, Tao, & Zhang, 2013;White, Hoogenboom, Kimball, & Wall, 2011). The crop models and their outputs are then used to guide agronomic decision-making aimed at sustainable management and development of adaptive strategies for responding to impacts of climate change (Basso et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In order to ensure today's food security and in the coming decades, efforts have been made on establishment of crop simulation models aimed at predicting growth, development and yield potential of a crop under certain environmental conditions (Basso et al, 2013;Wang et al, 2018;. Several dynamic crop simulations models (CSMs) have been developed and used widely to study physiological, physical and chemical processes of crop productivity under a changing climate (Kasampalis et al, 2018;Shi, Tao, & Zhang, 2013;White, Hoogenboom, Kimball, & Wall, 2011). The crop models and their outputs are then used to guide agronomic decision-making aimed at sustainable management and development of adaptive strategies for responding to impacts of climate change (Basso et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…NB: A brief review of crop yield estimation techniques can be found in the introduction to Doraiswamy et al (2005Doraiswamy et al ( , 2004Doraiswamy et al ( , 2003 and Kasampalis et al (2018) provide an overview of crop growth models.…”
Section: Indicator Example Methods Crop Yieldmentioning
confidence: 99%
“…The use of ad hoc methodological approaches according to different objectives, scales, sensors, temporal, and spatial resolutions represents an important achievement. The continuous exploitation of new technological resources is one of the main characteristics of rs+pheno science, which guarantees this discipline to be up-to-date and always evolving, according to the availability of innovative instruments, the development of novel methodologies, and the emergence of new questions [70].…”
Section: Major Research Topicsmentioning
confidence: 99%